Model Edukasi Sadari Berbasis IT sebagai Upaya Peningkatan Pengetahuan Deteksi Dini Kanker Payudara pada Wanita Usia Subur - Noviyanti, Aldila; Santoso, Bedjo; Sumarni, Sri; Santjaka, Aris; Widyawati, Melyana Nurul (Journal of Telenursing (JOTING), 2023)
This research aims to produce an IT-based Awareness Education Model as an effort to increase knowledge of early detection of breast cancer in women of childbearing age (WUS). The method used in this research is Research and Development (R&D) and model testing using a quasi-experiment design (pre and post-test with control group design). The results of the study showed that the increase in knowledge in the control group increased by 50.96% and in the intervention group there was an increase of 52.49% or in other words the intervention group experienced an increase of 1.39 times greater than the control group. Conclusion: Providing the IT-based Awareness education model is feasible to increase knowledge of early detection of breast cancer in women of childbearing age. Keywords: Application, Awareness, Knowledge, Attitude, Practice